KEPUASAN PELANGGAN TERHADAP PELAYANAN PEGAWAI JAMINAN KESEHATAN DAERAH (JAMKESDA) DI DINAS SOSIAL KOTA PEKANBARU - Yuliani Aprilia; Desti Irja; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to: (1) Know the level of customer satisfaction on the service of Health Insurance Employee Area (Jamkesda) in Pekanbaru City Social Service. (2) Knowing the most dominant aspect of customer satisfaction on the service of Health Insurance Employee Area (Jamkesda) in Pekanbaru City Social Service. (3) Knowing the variation of customer satisfaction level by sex, age, occupation, monthly amount of income. (4) Finding the greatest contribution of customer satisfaction on Health Service Employee Service Area (Jamkesda) at Pekanbaru City Social Service. This research is descriptive research with quantitative approach. The population in this study is the customer benefits that do extension in Pekanbaru City Social Service which amounted to 50 respondents. The sample technique used in this research is the incidental sampling this is because the research using the sample by chance. Sampling Insedental is a sample determination technique based on chance, ie anyone who accidentally / incidentally meets with the researcher can be used as a sample, when viewed by the person who happened to meet it is suitable as a data source. The instrument used is a questionnaire containing 37 statement items. customer satisfaction on the service of Health Insurance Employee (Jamkesda) in Pekanbaru City Social Service is measured by calculating total score of respondent answer based on indicator, that is: (1) emotional, (2) attitude, (3) comparison, (4) 5) hope. From result of research known that customer satisfaction to service of health insurance employee area (Jamkesda) in Pekanbaru City Social Service is high. The highest mean in one's expectation of something with mean 4.43 and SD 0.59 is then followed by the pleasure and displeasure of a person with mean 4.34 and SD 0.65 after which one's attitude toward something with mean 4.25 and SD 0 , 66 further comparison of what is accepted in reality with mean 4.23 and SD 0.63 and the indicator after which an emotional state of a person with a mean of 4.04 and SD 0.81. The meaning is the emotional state of a person is not very influential on customer satisfaction but one's expectations of something is very influential on customer satisfaction. Customers will feel happy in the service process if all their expectations are met.Keywords: Satisfaction Employee Service